Outcome of pediatric procedural sedation & analgesia in a tertiary care hospital in Pakistan - Jurair, Humaira (Pak J Med Sci, 2015)
BACKGROUND AND OBJECTIVE: Procedural sedation and analgesia (PSA) is pharmacologically induced state which allows patients to tolerate painful procedures while maintaining protective reflexes. It is the standard of care but there is limited data from Pakistan. Our objective was to assess the safety of the procedural sedation and analgesia in pediatric population at a tertiary care setting. METHODS: A retrospective notes and record review was conducted at the Aga Khan University Hospital, Karachi over 4 years from April 2010 to August 2014. Patients were between ages 6 months to 16 years and were in low risk category. The combination of Ketamine and Propofol were used. Data collected on the standardized hospital PSA form. All procedures were performed by two trained persons. RESULTS: A total of 3489 diagnostic and therapeutic procedures were performed. Satisfactory level of sedation was achieved for 3486 (99%) of procedures. Adverse events occurred in 21 (0.6%) patients including: 12 (0.3%) episodes of hypoxia, 07 (0.2%) episodes of apnea, 02 (0.06%) episodes of post sedation hallucination. No major events were noted. CONCLUSION: Procedural sedation & analgesia for children using Propofol and Ketamine is found safe and effective in our setting.